Microwave Synthesis of Chloroacetic Acid with Various Cocatalysts in Acetic Anhydride Catalyzing Method - Song, Guo-Qiang; Wang, Li-Sheng; Li, Fu-Xiang (Asian Journal of Chemistry, 2014)
In this paper, we introduce a method of synthesizing chloroacetic acid using acetyl chloride as catalyst and anhydrous ferric chloride, ferric chloride hexahydrate, zinc chloride and concentrated sulfuric acid (98 % H2SO4) as cocatalysts respectively with a variable frequency microwave oven as heater. From investigating the influences of cocatalysts in reaction, we draw a optimal condition that the yield and selectivity of chloroacetic acid are 98.11 and 98.58 % respectively when adding 0.4 g FeCl3 in mixture after reacting 3.5 h and in comparable with the corresponding percentages, 96.9 and 96.87 %, with 0.7 g ZnCl2 adding, the adding amount of 1.5 g 98 % H2SO4 result in a little lower percentages of 95.71 and 95.61 % correspondingly. We have speculated the cocatalytic mechanisms in chlorination.